State Governance and Implications for the Reforms of Market-economy Institutions in Vietnam - Hung, Nguyen Manh (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 34 No 1, 2018)
Over the last decade, the views that institutional reforms play an increasingly important role in the process of Doi Moi have been emerging in Vietnam. When factors such as natural resources, low-paid labor and capital etc., have reached their limit, institutional reforms thus become inevitable for economic growth. This however does not come without development challenge. Many countries embarking on institutional reforms were able to achieve only partial outcomes whereas some reform programs pushed the economy into unstable conditions. The success of economic institutional reforms would be limited without adequate efforts to establish a solid foundation for good governance.